Proapoptotic effects of novel thiazole derivative on human glioma cells. Issue 1 (January 2019) - Finiuk, Nataliya; Klyuchivska, Olha; Ivasechko, Iryna; Hreniukh, Volodymyr; Ostapiuk, Yuriy; Shalai, Yaryna; Panchuk, Rostyslav; Matiychuk, Vasyl; Obushak, Mykola; Stoika, Rostyslav; Babsky, Andriy
Abstract : The aim of the present study was to investigate the antiproliferative and proapoptotic actions of N -(5-benzyl-1, 3-thiazol-2-yl)-3, 5-dimethyl-1-benzofuran-2-carboxamide derivative (compound 5) in glioma cells in comparison with the actions of temozolomide (TMZ) and doxorubicin (Dox), used as positive controls. The antiproliferative activity of the compound 5, TMZ, and Dox on human glioblastoma U251 and human glioblastoma multiform T98G cells was measured using the MTT test. Western blot analysis, fluorescent microscopy, agarose gel retardation assay, flow cytometric analysis, and the DNA comet assay under alkaline conditions were carried out to study the effect of compound 5 on U251 cells. This compound showed 20 times higher cytotoxicity toward U251 and T98G cells compared with the effects of TMZ and approximately two times higher activity than that of the Dox. Compound 5 induced apoptosis in U251 cells by PARP1 and caspase 3 cleavage mechanisms, also inducing an increase in the level of Bax and Bim proapoptotic proteins and a decrease in the level of phosho-ERK1/2 kinase. The cytotoxicity of compound 5 was associated with an increase in the production of the hydrogen peroxide and the formation of DNA single-strand breaks. This compound 5 did not intercalate into a DNA molecule. Thus, the novel thiazole derivative (compound 5) proved to be a potential antiglioma drug that showed much higher cytotoxic action on human glioma cells compared with the effects of TMZ and Dox. Its cytotoxicity is associated with apoptosis induction, production of the reactive oxygen species, and formation of DNA single-strand breaks without significant DNA intercalation. Abstract : Supplemental Digital Content is available in the text.